Sustainable Fitness Park powered by expended energy of its users - Castillet, Lewis E.
At present, it has become a trend to incorporate a healthy routine, of setting aside time for exercise or other physical activities, into one's lifestyle. It is observable, especially in urban areas with designated green spaces, how many people participate in active outdoor activities. The number of fitness centers, gyms, and health clubs is increasing as well. Various physical activities happen in these places every day and great amount of energy is expended each day which can be converted to electricity. The purpose of this dissertation is to develop a public park with gym equipment and other physical activity devices that convert kinetic energy to electrical energy. The harvested electrical energy will be used to operate the public park. The main goal of the study is to promote the use of clean energy, physical fitness and the importance of a natural environment in urban areas. The study will look at relevant technologies available and combine these with different landscape elements to promote physical fitness for users. Keywords: Fitness Park, Kinetic Energy, Muscle Energy